REPRESENTATION AND SYMBOLISM OF FOLK MUSICAL INSTRUMENTS IN CONTEMPORARY UKRAINIAN NATIONAL CULTURE - Denkovych , Vasyl (Ukrainian Cultural Studies, 2023)
he article examines the issue of representation of Ukrainian folk instruments. The symbolic meaning of folk instruments is revealed, the connotations that demonstrate their deep implementation in the practice of creating national culture are highlighted. Such instruments as kobza, bandura, pipe, bugai, trembita are associated with the formation of the ethnic folk complex, which demonstrates the ability to be reincarnated in modern artistic practices. During their existence, they underwent changes in design, gained use in various musical stylistic directions. At the same time, they retained their significance as symbols of Ukrainian culture, independence and national pride. Unique musical instruments-symbols that have signs of belonging to Ukrainian culture and play an important role in the artistic space of today are considered. Their circulation in culture can be considered as a component of the integration of the nation and the connection of traditions and innovations. The analysis of Ukrainian folk instruments reveals their implementation in modern cultural genesis. Various musical instruments were a part of the life of our ancestors, performing various functions – from purely entertaining to communicative and warning. Currently, one can see the process of reviving interest in traditional musical instruments, which is accompanied by the transformation of the practices of their use. At the same time, the appeal to them acts as a factor of referring to the field of symbolic meanings, which these instruments embody, because of their traditional use. The timpani were a military signaling instrument and are currently perceived as a symbol of military life, the thirst for victory. Bandura and kobza, which were a symbol of the Cossacks, came to personify the fight against aggression. The bagpipe and trembita, which were the instruments of shepherds, have become members of modern bands in various stylistic directions, but their importance as carriers of the ethnic culture of Ukrainians is constant. A wider range of imagery and a symbol of national uniqueness are carried by instruments such as trembita and bugai. All of them represent the cultural heritage of Ukraine, demonstrating the ability to integrate and reproduce the nation